2005
DOI: 10.1016/j.bbabio.2004.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Composition of complex I from Neurospora crassa and disruption of two “accessory” subunits

Abstract: Respiratory chain complex I of the fungus Neurospora crassa contains at least 39 polypeptide subunits, of which 35 are conserved in mammals. The 11.5 kDa and 14 kDa proteins, homologues of bovine IP15 and B16.6, respectively, are conserved among eukaryotes and belong to the membrane domain of the fungal enzyme. The corresponding genes were separately inactivated by repeat-induced point-mutations, and null-mutant strains of the fungus were isolated. The lack of either subunit leads to the accumulation of distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 65 publications
0
48
0
Order By: Relevance
“…In silico analysis of the N. crassa genomic database (Neurospora Sequencing Project) led to the identification of the gene (NCU00278.5) encoding the 13.4L protein, which is a homologue of the described mammalian complex I assembly chaperone NDUFAF2 (20) and a paralog of the 13.4-kDa structural subunit of complex I (14). The single-copy gene is located on linkage group III of the fungal genome and comprises 2 exons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In silico analysis of the N. crassa genomic database (Neurospora Sequencing Project) led to the identification of the gene (NCU00278.5) encoding the 13.4L protein, which is a homologue of the described mammalian complex I assembly chaperone NDUFAF2 (20) and a paralog of the 13.4-kDa structural subunit of complex I (14). The single-copy gene is located on linkage group III of the fungal genome and comprises 2 exons.…”
Section: Resultsmentioning
confidence: 99%
“…Manipulation of N. crassa wild type strains 74-OR23-1A and 74-OR8-1a as well as of the complex I mutant strains nuo9.8 (24), nuo12.3 (25), nuo14 (14), nuo21 (26), nuo21.3a (27), nuo21.3c (28), nuo24 (17), nuo51 (18), and nuo78 (29) was performed according to standard procedures (30). The nuo13.4 (FGSC 13054a and FGSC 13055A), nuo18.4 (FGSC 15972a), and 13.4L (FGSC 11150a) mutant strains were obtained from the FGSC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wild-type N. crassa sequenced strain FGSC2489 (Galagan et al, 2003) and the gene deletion strains generated by the Neurospora Genome Project (Colot et al, 2006) were obtained from the Fungal Genetics Stock Center (FGSC) (McCluskey, 2003). The complex I mutant nuo14 (Marques et al, 2005), the AMID (DNCU06061; FGSC12090) deletion strain (Castro et al, 2008) and the general handling of the fungal strains (Davis & de Serres, 1970) have been described before. For the determination of drug sensitivity in spot assays, conidia from different strains were harvested with distilled water and adjusted to a concentration of 6.56610 7 cells ml 21 .…”
Section: Methodsmentioning
confidence: 99%
“…However, it was reported that a defect in a membrane arm subunit could prevent the proper formation of the peripheral arm (60). In the dum20 mutant of C. reinhardtii, the loss of ND1 prevents the assembly of any complex (55).…”
Section: Restoration Of Nadh Oxidation By Complex I In Cmsnad7mentioning
confidence: 99%